PENGARUH BIAYA PRODUKSI DAN BIAYA PENJUALAN TERHADAP LABA BERSIH PADA SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putra, Andri Eko; Oktariansyah, Oktariansyah; Rahayu, Dita (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to determine the effect of Production Cost and Sales Cost on the Net Profit of companies in the food and beverage sub-sector listed on the Indonesian Stock Exchange. The method in this study is the quantitative method. The population in this study includes 26 companies listed on the Indonesian Stock Exchange. Six companies were selected as the research sample. The data in this study is the secondary data obtained from audited annual reports and reported to the Indonesian Stock Exchange. The data analysis techniques in this study are classical hypothesis tests, i.e. normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, hypothesis testing, and coefficient of determination test. The results obtained from this study indicated that Production Costs have no significant influence on the Net Profit, while Sales Costs have a significant effect on the Net Profit, and at the same time, Production Costs and Sales Costs affect profits simultaneously. Keywords: Production Cost; Sales Cost; Net Profit